Reaksi Pasar terhadap Dividend Announcement Perusahaan yang Sahamnya Masuk Daftar Efek Syariah - Khoiruddin, Moh.; Faizati, Evy Rochfa (JDM (Jurnal Dinamika Manajemen), 2014)
The purpose of this study was to test the market reaction which was measured by abnormal return variable and trading volume activity (TVA) around the dividend announcement. The population of this study was all companiess dividendÂ announcement which their shares were listed on Indonesia Syariah Securities List published in 2013, they were 40 companies. The samples were taken from all population. The data were analyzed by one sample t-test to test the market reactions which occurred during event window for 21 days; they were t-10 (10 days before the dividend announcement), t0 (at the dividend announcement time), and t+10 (10 days after the dividend announcement). Based on the research results, it can be seen that there was a market reaction around the dividend announcement which was measured by abnormal returns variable and trading volume activity (TVA).